Pre-Descemet Corneal Dystrophy – Changes in Corneal Morphology in Confocal Microscopy - Urszula Kołodziejska; Anna K. Kurowska; Jacek P. Szaflik; Jerzy Szaflik (Okulistyka)
Purpose To identify and describe the in-vivo microstructural changes in the cornea of patients with pre-Descemet’s membrane corneal dystrophy.